PROBLEMS OF APPLICATION OF INNOVATIVE TECHNOLOGY ON THE BASIS OF LIGHTWEIGHT STEEL STRUCTURES IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the lightweight steel structures, their application in foreign countries, the essence of this technology, its creative qualities and shortcomings, as well as a brief overview of the current state of construction in the country on the basis of EPYUK The factors contributing to the development of construction technology in the direction and the proposals for their elimination